Strategi Guru dalam Memaksimalkan Pembelajaran Menulis Teks Eksplanasi di Sekolah Dasar - Agustin, Erina; Daeli, Kristian Ayu Pertiwi; Julianto, Indra Rasyid (Jurnal Cahaya Edukasi, 2025)
Indonesian language learning serves as a fundamental foundation for understanding all subjects. The role of the teacher in Indonesian language instruction is central in fostering students' knowledge and language skills, including listening, speaking, reading, and writing. This study aims to examine the efforts of Indonesian language teachers in guiding students in writing explanatory texts in the sixth-grade Indonesian language class at SDN Nalagati and to identify the factors that hinder teachers' efforts in assisting students in writing explanatory texts.  An explanatory text is a type of text that provides an explanation of a particular phenomenon or process, requiring specific skills in its composition and delivery. In this context, teachers play a crucial role in helping students understand the structure of explanatory texts, which consists of the purpose, sequence of explanations, and conclusion. Through appropriate approaches, such as the use of suitable learning media and the application of varied teaching methods, teachers can enhance students' ability to write clear and well-structured explanatory texts.  Based on a variety of literature studies, using diverse teaching approaches has been shown to accelerate students' understanding of explanatory text writing techniques. These methods include using picture series media, process-based approaches, developing animated video media, applying the Contextual Teaching and Learning (CTL) method, implementing the RADEC model, utilizing the cooperative STAD method, and incorporating audiovisual media. Therefore, a teacher’s ability to design and implement interactive learning strategies significantly influences the quality of students' learning outcomes in writing explanatory texts.